Role of Multislice Computed Tomography and Local Contrast in the Diagnosis and Characterization of Choanal Atresia - Khaled Al-Noury; Alsaid Lotfy (International Journal of Pediatrics)
Objective. To illustrate the role of multislice computed tomography and local contrast instillation in the diagnosis and characterization of choanal atresia. To review the common associated radiological findings. Methods. We analyzed 9 pediatric patients (5 males and 4 females) with suspected choanal atresia by multislice computed tomography. We recorded the type of atresia plate and other congenital malformations of the skull. Results. Multislice computed tomography with local contrast installed delineated the posterior choanae. Three patients had unilateral mixed membranous and bony atresia. Three patients had unilateral pure bony atresia. Only 1 of 7 patients have bilateral bony atresia. It also showed other congenital anomalies in the head region. One patient is with an ear abnormality. One patient had congenital nasal pyriform aperture stenosis. One of these patients had several congenital abnormalities, including cardiac and renal deformities and a hypoplastic lateral semicircular canal. Of the 6 patients diagnosed to have choanal atresia, 1 patient had esophageal atresia and a tracheoesophageal fistula. The remaining patients had no other CHARGE syndrome lesions. Conclusions. Local Contrast medium with the application of the low-dose technique helps to delineate the cause of the nasal obstruction avoiding a high radiation dose to the child.